The potential sources of foreign language reading anxiety in a Jordanian EFL context: a theoretical framework - Sheikh Ahmad, Ismail; Al-Shboul, Murad M.; Nordin, Mohamad Sahari; Abd Rahman, Zainurin; Ibrahim, Mohd Burhan; Madarsha, Kamal Basha (Canadian Centre for Science and Education, 2013)
The last decade has witnessed an increasing research trend on foreign language reading anxiety as a skill related to but distinct from foreign language anxiety. However, sources of foreign language reading anxiety have rarely been investigated. Thus, the current study responds to the study by (Saito, Horwitz, & Garza, 1999) and extends the work of (Al-Shboul, Ahmad, Nordin, & Rahman, 2013b) in this specific area to propose a theoretical framework that represents the sources of foreign language reading anxiety and to measure the extent of those sources in the Jordanian EFL context. A cross-sectional survey of 1500 undergraduate students who were taking Basic English courses was administered. A total of 1006 questionnaires were valid for analysis. However, only 408 questionnaires were randomly chosen according to the criteria of quota sampling techniques. The proposed theoretical framework was tested to measure the prevalence of the sources of foreign language reading anxiety to reveal that there were two aspects of foreign language reading anxiety: personal factors and text features. Under the concept of personal factors, there were two main sources of foreign language reading anxiety; afraid of making errors and worry about reading effects. On the other hand, there were three main sources of foreign language reading anxiety under the concept of text features; unknown vocabulary, unfamiliar topic, and unfamiliar culture. Implications to the study and recommendations for further research were considered. Keywords: sources of foreign language reading anxiety, foreign language reading anxiety, Jordanian EFL Context, Yarmouk University, theoretical framework